2013
DOI: 10.1590/s1516-89132013000400012
|View full text |Cite
|
Sign up to set email alerts
|

Role of killer factors in the inhibitory activity of bio-control yeasts against Penicillium expansum and Aspergillus ochraceus

Abstract: This work evaluated the antagonism of killer positive yeast strains (isolated from 11 samples of different frozen fruit pulps) against the strains of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…In general, killer toxins are able to determine death or inhibit growth of other microbial cells through a target-specific mode of action [15]. Chemically, the killer toxins are glycoproteins or extracellular proteins that can inhibit cell membrane functions in susceptible pathogenic yeasts or other microorganisms, a process mediated by specific receptors present in the cell wall of susceptible microorganisms [16]. From a genetic point of view, the killer toxins can be encoded by dsRNA molecules, DNA plasmids or by chromosomal genes.…”
Section: Killer Yeastsmentioning
confidence: 99%
“…In general, killer toxins are able to determine death or inhibit growth of other microbial cells through a target-specific mode of action [15]. Chemically, the killer toxins are glycoproteins or extracellular proteins that can inhibit cell membrane functions in susceptible pathogenic yeasts or other microorganisms, a process mediated by specific receptors present in the cell wall of susceptible microorganisms [16]. From a genetic point of view, the killer toxins can be encoded by dsRNA molecules, DNA plasmids or by chromosomal genes.…”
Section: Killer Yeastsmentioning
confidence: 99%
“…The mechanisms of action of killer toxins on fungi include inhibition of β-glucan synthesis or hydrolysis of β-glucan in the cell wall of susceptible strains, disruption of cell division by blocking DNA synthesis, tRNA cleavage, blocking calcium uptake, and ion leakage caused by the formation of channels in the cytoplasmic membrane [41]. Da Silva Portes et al [66] showed that killer toxins isolated from the yeast of the genus Kluyveromyces could be used in the biocontrol of the pathogenic fungi P. expansum and A. ochraceus, and that they exerted their action by inhibiting spore germination and limiting mycelium growth. The activity of the yeast S. cerevisiae, possibly related to its ability to secrete killer toxins, was also used to control the toxigenic fungi A. flavus and A. parasiticus [49].…”
Section: Production Of Antifungal Metabolites and Volatile Compoundsmentioning
confidence: 99%
“…Portes et al (2013) também avaliaram o antagonismo das leveduras Candida globrata, C. albidans, S. cerevisiae e Pichia kluyveri, produtoras de toxina killer contra P. expansum e Aspergillus ochraceus, observando que tal produção foi eficiente no controle dos dois fitopatógenos.…”
Section: /11unclassified